Analysis of oil price, trade openness and business cycle on exchange rate in Indonesia - Kurniawan, Mahrus Lutfi Adi; Trianto, Cahyo; Suripto, Suripto (Jurnal Ekonomi & Studi Pembangunan, 2024)
The importance of exchange rate stability in achieving macroeconomic policy objec-tives cannot be ignored by developed or developing countries, including Indonesia. The adaptability of exchange rate management policies in achieving the macroeco-nomic policy goals is a testament to the resilience of the system. However, exchange rate stability cannot occur by itself, it depends on macroeconomic conditions. The research applies the ARDL method to analyze the short and long term influence of macroeconomic variables on exchange rates. The research results show that oil pric-es have a negative and significant impact on the rupiah exchange rate in the long term, while trade openness has no effect in the short and long term. The ARDL model consistently shows the negative influence of business cycle variables on ex-change rates in the short and long term.The implication of the research is that maintaining the stability of domestic macroeconomic conditions through increasing people's purchasing power, encouraging exports and export diversification, especial-ly in the manufacturing sector, which not only has a large multiplier effect in ab-sorbing labor but also can be a significant tool for stabilizing the exchange rate.